2013
DOI: 10.1111/vop.12126
|View full text |Cite
|
Sign up to set email alerts
|

Differences in ocular parameters between diurnal and nocturnal raptors

Abstract: Phenol red thread test and STT are both valid methods to measure tear production; however, a separate baseline must be determined for each species using these methods, as the results of one method cannot be extrapolated to the other. Due to significant differences observed within diurnal and nocturnal species, it appears that a more intricate division should be used when comparing these parameters for raptors, and the classification of diurnal or nocturnal holds little significance in the baseline of these dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
(37 reference statements)
5
21
2
Order By: Relevance
“…It was found that the modified strip, as previously described (da Silva et al 2013), was tolerated by the animals, without causing excessive stress. The STT has shown restrictions when used in small eyes (Willis & Wilkie 1999, Müller et al 2010, Beckwith-Cohen et al 2015 which also was observed in the present study (Lange et al 2012, Da Silva et al 2013). According to Williams (2012), the use of a modified strip (cut in half with width of 2.5 mm) is a viable option in species of birds with small eyes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It was found that the modified strip, as previously described (da Silva et al 2013), was tolerated by the animals, without causing excessive stress. The STT has shown restrictions when used in small eyes (Willis & Wilkie 1999, Müller et al 2010, Beckwith-Cohen et al 2015 which also was observed in the present study (Lange et al 2012, Da Silva et al 2013). According to Williams (2012), the use of a modified strip (cut in half with width of 2.5 mm) is a viable option in species of birds with small eyes.…”
Section: Discussionsupporting
confidence: 76%
“…Given the difficulties described for the use of the STT strip (Willis & Wilkie 1999, Müller et al 2010, Beckwith--Cohen et al 2015 or even mSTT strip (Williams 2012, Kern & Colitz 2013, Somma et al 2015, Meekins et al 2015, some authors suggest the use of the phenol red test (Willis & Wilkie 1999, Kern & Colitz 2013, Beckwith-Cohen et al 2015. Although this test is well tolerated by birds (Bliss et al 2015), low reproducibility has been reported in large Psitacciformes (Holt et al 2006), and better PRT reproducibility on A. ventralis (Storey et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the systematic review was to collect typical IOPs for healthy adult species of vertebrates; therefore, some aspects of the variations in IOP within each group of vertebrates were not included in the study. While in healthy animals the IOP is generally not significantly different in the left and right eye [ 40 , 41 , 43 , 53 , 56 59 , 64 66 , 69 , 74 76 , 79 , 85 , 88 , 91 , 92 , 98 , 103 , 111 , 114 , 114 , 117 , 122 127 , 132 ] or in males and females [ 41 , 43 , 56 , 58 , 63 , 65 , 69 , 74 , 75 , 79 , 85 , 88 , 91 , 92 , 103 , 114 , 121 124 , 126 , 132 , 133 ], it has been found to change with position in flamingos and bats. [ 59 , 60 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IOP was also found to change with age in some species [ 41 , 56 , 63 ]. While no statistical correlation between IOP and body weight was found in raptors [ 53 ], Long-Eared Hedgehog [ 88 ] and juvenile Yacare Caiman [ 133 ], a moderate statistically significant negative correlation was found in Gulf-Coast Box Turtles and Three-Toed Turtles [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Birds of prey and caimans generally produce less tear fluid than humans or dogs [23][24][25]. As this fluid can only be collected in small quantities, the collection method must be precise.…”
Section: Discussionmentioning
confidence: 99%